Examining moral injury and posttraumatic stress among firefighters, emergency medical services personnel, and emergency dispatchers - Savannah J. Woller; Kayla E. Hall; Shelby J. McGrew; Elizabeth Anderson-Fletcher; Sonya B. Norman; Anka A. Vujanovic (European Journal of Psychotraumatology)
Background First responders encounter chronic exposure to stressful and potentially traumatic experiences due to the nature of their jobs. First responders are also often confronted with the dilemma of following organisational protocols and/or using personal judgment to respond in high stress situations. Thus, posttraumatic stress disorder (PTSD) and moral injury (MI), defined as the negative impact of witnessing, perpetrating, or failing to prevent an act that violates one’s moral beliefs, are potential psychological responses to potentially traumatic events.Objective The present study evaluated MI severity among firefighters, emergency medical services (EMS) personnel, and dispatchers with and without probable PTSD.Method The sample included 283 personnel (Mage = 46.53; 83.7% male) from nine fire departments, primarily in the western US.Results Consistent with hypotheses, first responders who met screening criteria for probable PTSD, as compared to those who did not, reported significantly higher MI total scores, MI-shame subscale scores, and MI-trust-violation subscale scores, with large effect sizes (η2’s ≤ .22).Conclusions Results suggest that MI may play a role in the characterisation of the clinical picture of first responders. Future studies should continue to evaluate associations between PTSD and MI in first responders, using interview-based and longitudinal methodologies, to better inform specialised clinical interventions.